Odpowiedź :
a)
[tex] \frac{1}{2} + 1\frac{5}{6} = \frac{3}{6} + 1 \frac{5}{6} = 1 \frac{8}{6 } = 2 \frac{2}{6} = 2 \frac{1}{3} [/tex]
[tex] \frac{2}{3} + 1 \frac{5}{6} = \frac{4}{6} + 1 \frac{5}{6} = 1 \frac{9}{6} = 2 \frac{3}{6} = 2 \frac{1}{2} [/tex]
[tex]2 \frac{1}{12} + 1 \frac{5}{6} = 2 \frac{1}{12} + 1\frac{10}{12} = 3 \frac{11}{12} [/tex]
[tex]1 \frac{3}{4} + 1 \frac{5}{6} = 1 \frac{9}{12} + 1 \frac{10}{12} = 2 \frac{19}{12} = 3 \frac{7}{12} [/tex]
[tex]1 \frac{1}{5} + 1 \frac{5}{6} = 1 \frac{6}{30} + 1 \frac{25}{30} = 2 \frac{31}{30} = 3 \frac{1}{30} [/tex]
[tex]2 \frac{7}{8} + 1 \frac{5}{6} = 2 \frac{21}{24} + 1 \frac{20}{24} = 3 \frac{41}{24} = 4 \frac{17}{24} [/tex]
[tex]3 \frac{4}{9} + 1 \frac{5}{6} = 3 \frac{8}{18} + 1 \frac{15}{18} = 4 \frac{23}{18} = 5 \frac{5}{18} [/tex]
b)
[tex]1 \frac{9}{10} - \frac{3}{5} = 1 \frac{9}{10} - \frac{6}{10} = 1 \frac{3}{10} [/tex]
[tex]2 \frac{1}{15} - \frac{3}{5} = 2 \frac{1}{15} - \frac{9}{15} = 1 \frac{16}{15} - \frac{9}{15} = 1 \frac{7}{15} [/tex]
[tex]1 \frac{1}{3} - \frac{3}{5} = 1 \frac{5}{15} - \frac{9}{15} = \frac{20}{15} - \frac{9}{15} = \frac{11}{15} [/tex]
[tex] \frac{3}{4} - \frac{3}{5} = \frac{15}{20} - \frac{12}{20} = \frac{3}{20} [/tex]
[tex]4 \frac{1}{2} - \frac{3}{5} = 4 \frac{5}{10} - \frac{6}{10} = 3 \frac{15}{10} - \frac{6}{10} = 3 \frac{9}{10} [/tex]
[tex]5 \frac{7}{20} - \frac{3}{5} = 5 \frac{7}{20} - \frac{12}{20} = 4 \frac{27}{20} - \frac{12}{20} = 4 \frac{15}{20} = 4 \frac{3}{4} [/tex]
[tex]1 \frac{3}{7} - \frac{3}{5} = 1 \frac{15}{35} - \frac{21}{35} = \frac{50}{35} - \frac{21}{35} = \frac{29}{35} [/tex]
Myślę że pomogłem ;)